DAMPAK DEBT TO ASSETS RATIODAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSETS - Juan Anastasia Putri; Hery Pandapotan Silitonga; Ady Inrawan (Faculty of Economic and Business Universitas STIKUBANK, 2020)
the purpose of this research is to know debt to assets ratio (roa) and debt to equity ratio (der) to return on assets (roa). data analysis technique used is the classic assumption test, multiple linear regression, coefficient of determination, f test and t test. objects in the metal sub sector sector and the like which are listed on the indonesia stock exchange in 2016-2018. the results of the study can be concluded as follows: 1. the results of multiple linear regression analysis test results obtained dar has a positive effect and der has a negative effect on roa. 2. determination results of 19%, this means that the dar and der can affect the roa of 19% 3. hypothesis tests, for the f test results obtained dar and der have a significant effect on roa, and t test that the dar has a positive and insignificant effect on roa, and and the der has a negative effect and no significant roa. Keyword: DAR, DER, ROA